Cancer incidence among Finnish world class male athletes - Pukkala, E.; Kaprio, J.; Koskenvuo, M.; Kujala, U.; Sarna, S. (International Journal of Sports Medicine, 2000)
A cohort of 2269 male world class athletes from the years 1920-65 was followed up through the Finnish Cancer Registry for cancer incidence during 1967-95. There were 331 cases of cancer while the expected number based on the national cancer incidence rates was 404; the standardized incidence ratio (SIR) was 0.82 and its 95% confidence interval (CI) 0.73-0.91. There was a decreased risk of cancers of the lung (SIR 0.35, 95% CI 0.25-0.48), especially among endurance athletes (0.12, 0.01-0.41). This fits well with the low prevalence of smoking among the athletes. The SIR for kidney cancer was also significantly low (0.43, 0.16-0.93), possibly partly due to the better diet (more vegetables, less fat). Incidence of cancers not related to smoking was not reduced. None of the cancer sites showed a significant excess in the whole cohort but hurdlers had a significantly high relative risk of sarcomas of the bone and soft tissue which according to suggested causal mechanisms might be related e.g. to injuries during their active sport period. This as well as other observations without sound a priori hypotheses needs to be confirmed in more detailed analyses and in other data sets before final conclusions.